It's your move : my million dollar method for taking risks with confidence and succeeding at work and life - Altman, Josh, 1979- (Tantor Audio, 2016)
One of the stars of Bravo's hit series Million Dollar Listing Los Angeles reveals his trade secrets, offering aspiring entrepreneurs and established professionals tips and insights to help them outsmart the competition.